A High-Resolution Study of the 110Tc → 110Ru → 110Rh → 110Pd Decay Chain with the GRETINA Array. (December 2020) - Jazrawi, S.; Doherty, D.T.; Allmond, J.M.; Regan, P.H.; Janssens, R.V.F.; Korten, W.; Zhu, S.; Zielińska, M.; Radford, D.; Ansari, S.; Auranen, K.; Bucher, B.; et al.
Abstract: Spectroscopic data, such as precise γ-ray branching and E 2/ M 1 multipole-mixing ratios, provide vital constraints when performing multi-dimensional Coulomb-excitation analyses. Consequently, as part of our new Coulomb-excitation campaign aimed at investigating the role of exotic non-axial (triaxial) deformations in the unstable refractory Ru-Mo isotopes, additional beta-decay data was obtained. These measurements make use of ANL's CARIBU facility, which provides intense beams of radioactive refractory isotopes along with the excellent efficiency and angular resolution of the GRETINA γ-ray tracking array. In this article, we report on the analysis of the A = 110 decay chain, focussing on the identification of previously unreported states in 110 Ru following the decay of 110 Tc.